The Impact Of Auditor's Fees Size On Audit Quality field Study In The Audit Offices Working In Damascus (Journal of Hama University, 2019)
This paper seeks to contribute to the clarification of one of the most important audit literature, based on the research presented in the same subject, or in one of its parts, by examining the effect of the fees size of the auditors and audit offices on the quality of the audit process they provide to audit clients, As the responsibility of the external auditor is to ensure the quality, integrity, and suitability of the financial statements to the end-users. Financial reporting users view the auditor as independent, objective and impartial during the preparation of his financial reports, and therefore his review process must be of quality to the approval of the mental image that clients have about references and practices. This paper, through the field study conducted in the top 10 accounting firms in Damascus, has reached several results:• There are differences in the sample of the study regarding audit fees and the quality of the audit, due to the demographic variables (gender, age, experience, qualification).2. The size of the auditor's fees affects the quality of the audit, as the relationship between the two variables has emerged in an inverse medium relationship.